2016
DOI: 10.1111/adb.12405
|View full text |Cite
|
Sign up to set email alerts
|

Differential behavioral and molecular alterations upon protracted abstinence from cocaine versus morphine, nicotine, THC and alcohol

Abstract: Unified theories of addiction are challenged by differing drug-seeking behaviors and neurobiological adaptations across drug classes, particularly for narcotics and psychostimulants. We previously showed that protracted abstinence to opiates leads to despair behavior and social withdrawal in mice, and we identified a transcriptional signature in the extended amygdala that was also present in animals abstinent from nicotine, i9-tetrahydrocannabinol (THC) and alcohol. Here we examined whether protracted abstinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 84 publications
11
51
0
Order By: Relevance
“…(d) Depiction of DH areas where Fos was counted, representative image from Bregma − 3.14 (Paxinos and Watson, 2006). cocaine-naive subjects (Becker et al, 2016) such that increased Fos during ED1 may reflect a return to baseline Fos levels. Regardless, our findings that Fos levels correlate with ED1 responding in many regions indicate that such activation may play an important role in ED1 drug seeking.…”
Section: Intakementioning
confidence: 99%
“…(d) Depiction of DH areas where Fos was counted, representative image from Bregma − 3.14 (Paxinos and Watson, 2006). cocaine-naive subjects (Becker et al, 2016) such that increased Fos during ED1 may reflect a return to baseline Fos levels. Regardless, our findings that Fos levels correlate with ED1 responding in many regions indicate that such activation may play an important role in ED1 drug seeking.…”
Section: Intakementioning
confidence: 99%
“…Repeated exposure to morphine increases levels of anxiety both in humans and in animal models of substance use disorders (Gold et al, 1978;1979;Becker et al, 2017). Additionally, it is posited that relapse to opioids in abstinent patients is caused by negative affective states driving negative reinforcement (Solomon and Corbit, 1978;Koob and Le Moal, 2008;Evans and Cahill, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Morphine possesses anxiolytic-like properties during initial exposure (Koks et al, 1999;Sasaki et al, 2002;Shin et al, 2003). However, during opioid abstinence, symptoms of anxiety (Gold et al, 1978;1979;Li et al, 2009;Shi et al, 2009) or anxiety-like behaviors are observed (Cabral et al, 2009;Becker et al, 2017). Here, we show that 24 h following repeated morphine injections (once a day for 5 days), mice display anxiety-like behaviors in the elevated plus maze (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, opioid dependent patients have a high incidence of depression. Indeed, opioid use in the absence of pain has been shown to induce a protracted abstinence syndrome [25,26], and can increase the likelihood of major depressive episodes [27]. There is also recent evidence that long-term prescription opioid use is associated with both new onset and recurrence of depression [28], as well as enhances the risk of developing treatment resistant depression [29 • ].…”
Section: Hypodopaminergia Driven By Neuroinflammation Is a Shared Phementioning
confidence: 99%